2017
DOI: 10.1080/07357907.2017.1337783
|View full text |Cite
|
Sign up to set email alerts
|

Role of GSK-3β in Regulation of Canonical Wnt/β-catenin Signaling and PI3-K/Akt Oncogenic Pathway in Colon Cancer

Abstract: Non-steroidal anti-inflammatory drugs (NSAIDs) are emerging as novel chemopreventive agents because of their ability in blocking cellular proliferation, and thereby tumor development, and also by promoting apoptosis. GSK-3β, a serine threonine kinase and a negative regulator of the oncogenic Wnt/β-catenin signaling pathway, plays a critical role in the regulation of oncogenesis. Celecoxib and etoricoxib, the two cyclooxygenase-2 (COX-2) selective NSAIDs, and Diclofenac, a preferential COX-2 inhibitory NSAID, h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 36 publications
1
30
0
Order By: Relevance
“…The activation of AKT/mTOR involves phosphorylation of AKT and mTOR. Interestingly, studies have shown that activated AKT could result in phosphorylation and inactivation of GSK3β [13,14], which therefore promotes β-catenin accumulation and nuclear translocation in Wnt/β-catenin pathway [15]. These previous findings indicate the crosstalk between AKT/mTOR and Wnt/β-catenin signaling pathways, and the regulation of these two pathways has also been reported in several cancers [16,17].…”
Section: Introductionmentioning
confidence: 75%
See 2 more Smart Citations
“…The activation of AKT/mTOR involves phosphorylation of AKT and mTOR. Interestingly, studies have shown that activated AKT could result in phosphorylation and inactivation of GSK3β [13,14], which therefore promotes β-catenin accumulation and nuclear translocation in Wnt/β-catenin pathway [15]. These previous findings indicate the crosstalk between AKT/mTOR and Wnt/β-catenin signaling pathways, and the regulation of these two pathways has also been reported in several cancers [16,17].…”
Section: Introductionmentioning
confidence: 75%
“…Former studies have delineated that AKT/mTOR pathway and Wnt/β-catenin pathway are key pattern regulating cancer progression [12,26], including in cervical cancer [18,19]. Also, several studies have revealed the crosstalk of these two pathways by demonstrating that p-AKT could induce the phosphorylation GSK3β so as to inhibit GSK3β [13,14], which consequently leads to β-catenin accumulation and nuclear migration, thus activating Wnt/β-catenin pathway [15]. Our study first related GHET1 to AKT/mTOR and Wnt/β-catenin pathways in CC by showing that down-regulating GHET1 reduced the activities of AKT/mTOR pathway and Wnt/β-catenin pathway.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different components and targets of the Wnt canonical pathway were evaluated by RT-qPCR. It was shown that Akt may inhibit GSK3β, which is a repressor of β-Catenin transcription factor [30]. GSK3β mRNA expression presented an expected opposite pattern of expression compared to β-Catenin (CTNNB1) mRNA.…”
Section: Emt: Wnt Canonical Pathwaymentioning
confidence: 99%
“…Recently, the biological effects of small molecule compounds on GSK-3β were widely studied for its potential value on CRC treatment. It is reported that activation of GSK-3β while downregulating the PI3-K/Akt oncogenic pathway by non-steroidal anti-inflammatory drugs (NSAIDs), results uniformly in the chemopreventive and anti-neoplastic effects in the early stage of colon cancer (45). In the present study, treated with BIO in CRC cells, the expression levels of p-GSK-3β (Tyr 216) were decreased both in CRC SW480 and SW620 cells, demonstrating that GSK-3β activity was significantly inhibited by BIO.…”
Section: Discussionmentioning
confidence: 99%